Hubungan Persepsi Keselamatan dan Kesehatan Kerja (K3) dan Sikap Siswa dalam Praktek terhadap Hasil Belajar Mata Pelajaran Teknik Pengelasan Kelas XI di SMK Negeri 1 Bangkinang - Nazrian Arham; Andre Kurniawan; Syahril; Irzal (Lembaga Yasin AlSys, 2026)
Although the implementation of occupational safety and health (OSH) in vocational education has been widely studied, evidence regarding the simultaneous relationship of OSH perceptions and students’ attitudes during practical activities with welding learning outcomes remains limited. This study aimed to analyze the relationships of OSH perceptions and students’ attitudes during practical activities with the Welding Engineering learning outcomes of Grade XI students at SMK Negeri 1 Bangkinang. The study employed a quantitative approach with a correlational design. A total of 60 students were included as the sample using total sampling. Data were collected using questionnaires on OSH perceptions and students’ attitudes, as well as documentation of practical assessment scores, and were then analyzed using Pearson correlation and multiple linear regression. The results showed that OSH perceptions were positively and significantly correlated with learning outcomes (r = 0.272; p = 0.036). Students’ attitudes during practical activities were also positively and significantly correlated with learning outcomes (r = 0.284; p = 0.028). Simultaneously, OSH perceptions and students’ attitudes were significantly related to learning outcomes (R = 0.357; R² = 0.127; p = 0.021), with a contribution of 12.7%. These findings confirm that practical learning outcomes in vocational education are related not only to technical skills but also to students’ safety awareness and work attitudes. This study provides practical implications for schools to strengthen the OSH culture, improve supervision during practical learning, and ensure the availability of personal protective equipment. Future studies need to involve larger samples and consider other supporting variables.